New TOEIC speaking coach (Tổng hợp Thành phố Hồ Chí Minh, 2011)
New TOEIC Speaking Coach Contents: Chapter 1: Read a text aloudUnit 1: Description of question type Unit 2: Troublesome soundsUnit 3: Practicing PluralsUnit 4: "Pronouncing" PunctuationUnit 5: Imitate a recording Unit 6: Using Prep Time to Rehearse Problem Words